Patients With Autism Spectrum Disorder and Co-occurring Substance Use Disorder: A Clinical Intervention Study - Sharon JN Walhout; Johan van Zanten; Laura DeFuentes-Merillas; Christina KME Sonneborn; Marc Bosma (SAGE Publishing, 2022)
Background: The prevalence of substance use disorders (SUD) in individuals with autism spectrum disorders (ASD) appears to be higher than previously described. Attention has been drawn to developing new treatment approaches for this patient population, as they appear to do less well with traditional addiction treatment. There is very little research addressing treatment outcome. This study aims to introduce and evaluate a manualized group treatment intervention developed specifically for patients with ASD and co-occurring SUD. Methods: We developed a group treatment based on cognitive behavioural therapy (CBT) and evaluated outcome measures at the end of treatment and 3-month follow-up. Fifty-seven patients with ASD and co-occurring SUD were included of which 30 completed the group intervention, 27 of them also participated at 3-month follow-up. Results: The findings suggest that group treatment can work for patients with ASD and co-occurring SUD. Lower levels of alcohol use ( t  = 3.61, P  = .002, d  = 0.75), craving ( t  = 2.65, P  = .013, d  = 0.51), passive coping styles ( t  = 2.32, P  = .030, d  = 0.48), depression ( t  = 3.48, P  = .002, d  = 0.67), anxiety ( t  = 3.02, P  = .006, d  = 0.58), and stress ( t  = 2.62, P  = .015, d  = 0.51) symptoms were reported after completing the group intervention, with even stronger effects at 3 months follow-up. Conclusions: The present study shows promising results of a tailor-made group intervention in a heterogeneous patient population with ASD and co-occurring SUD with positive effects on both symptoms of ASD and SUD.